Multi-phased internalization of murine norovirus (MNV) in Arabidopsis seedlings and its potential correlation with plant defensive responses. (October 2019) - Kim, Kangmin; Yadav, Dhananjay; Cho, Min
Abstract: Norovirus is a highly infectious human pathogen that causes acute foodborne diseases worldwide. As global diet patterns have begun to incorporate a higher consumption of fresh agricultural products, the internalization of norovirus into plants has emerged as a potential threat to human health. Here, we demonstrated that murine norovirus (MNV1) was internalized into Arabidopsis in multiple phases, and this internalization was correlated with Arabidopsis innate immunity responses. Under hydroponic conditions, continuous treatment of MNV1 retarded root growth and facilitated flower development of Arabidopsis without causing necrotic lesions. Examination of viral titers and RNA levels revealed that MNV1 was internalized into Arabidopsis in at least three different phases. In response to MNV1 treatment, the Arabidopsis defensive marker PR1 (a salicylic acid signaling marker) was transiently up-regulated at the early stage. PDF1.2, a jasmonic acid signaling marker, exhibited a gradual induction over time. Noticeably, Arabidopsis RNS1 (T2 ribonuclease) was rapidly induced by MNV1 and exhibited anti-correlation with the internalization of MNV1. Exposure to recombinant Arabidopsis RNS1 protein reduced the viral titers and degraded MNV1 RNA in vitro . In conclusion, the internalization of MNV1 into Arabidopsis was fluctuated by mutual interactions that were potentially regulated by Arabidopsis immune systems containing RNS1 . Highlights: MNV1 treatment altered the root growth and floral transition of Arabidopsis . The internalization of MNV1 into Arabidopsis occurred in multiple phases. Plant immune responses potentially modulated the MNV1 internalization. Arabidopsis ribonuclease RNS1 negatively regulated MNV1.